Role of diffusion tensor imaging of sciatic nerve in symptomatic patients with inconclusive lumbar MRI. Issue 131 (October 2020) - Foti, Giovanni; Lombardo, Fabio; Fighera, Alessandro; Giaretta, Alvise; Catania, Matteo; Serra, Gerardo; Carbognin, Giovanni
Abstract: Objective: To assess fractional anisotropy (FA) of sciatic nerve roots within the pelvis by using diffusion tensor imaging (DTI) in patients suffering from sciatica with inconclusive lumbar MRI. Methods: This IRB-approved prospective study included 32 consecutive subjects (11 males and 21 females; mean age 32.2 years) between September 2019 and February 2020. All patients underwent DTI (TR/TE 5800/97 ms; b = 1000; slice thickness 3, 5 mm; directions = 20) on a 1.5 T scanner (Siemens Aera). Seventeen patients were symptomatic, whereas 15 patients served as control group. DTI data were analyzed by two radiologists (25 and 11 years of experience, respectively) blinded to clinical data. Each radiologist placed two ROIs on the nerve roots at three different levels. Diagnostic accuracy values of FA numbers were calculated by using receiver operator curves (ROC) and relative area under the curve (AUC), by using clinical findings as standard of reference. Inter-observer agreement was calculated with k-statistics. Paired T-test and Mann-Whitney test were used for comparison accordingly to data distribution. A value of p < 0.05 was considered statistically significant. Results: Among the 17 symptomatic patients, FA values were significantly lower in the affected side at all levels (p < 0.05). The FA ratio (FA affected side/FA unaffected side) of symptomatic patients was significantly lower compared to control group at level 1 (p = 0.0005) and level 2 (p = 0.0006). Using a threshold of 0.90 for level 1 and 0.73 for level 2, 76 % and 71 % sensitivity and 100 % and 87 % specificity were achieved, respectively. Conclusion: DTI can quantitatively demonstrate sciatic nerve roots impairment within the pelvis.